Granulomatous lung disease in two workers making light bulbs. Issue 10 (26th July 2019) - Ronsmans, Steven; Verbeken, Eric K; Adams, Els; Keirsbilck, Stephan; Yserbyt, Jonas; Wuyts, Wim A; Swennen, Rudy; Hoet, Peter HM; Nemery, Benoit
Abstract: Background: Associations between sarcoidosis or sarcoid‐like granulomatous lung disease and exposure to silica and other inorganic agents have been suggested in several studies. Cases: We describe granulomatous lung disease in two workers of a small production unit making metal‐halide lamps. Initially, both were diagnosed with sarcoidosis. However, in both men, birefringent particles were observed in the lung or mediastinal lymph node biopsies. Clipping of glass tubes led to moderate exposure to dust, consisting mainly of amorphous fused silica, with some cristobalite. After removal from exposure, both subjects improved clinically, radiologically, and functionally. Conclusion: The present cases support the hypothesis that silica might be a trigger for sarcoid‐like granulomatous lung disease. Sarcoidosis should be considered a diagnosis of exclusion and clinicians should carefully collect occupational and environmental exposure histories to identify workplace triggers.